Upaya Pengelolaan Sampah Di Kampus Stt-Pln Dengan Teknologi Anaerobik Digester - Ranti Hidayawanti; Irma Wirantina Kustantrika; Endah Lestari (KILAT, 2017)
In urban areas are faced with various problems are quite complex especially in waste management. One of issues that arises is the high rate of landfill waste, public awarness as human behavior is still ery low as well as problems in the final waste disposal activities which often creates problems of its own. Campus area produces organic and inorganic waste in large numbers, as we knows organic waste content of high organic content and can be caused of pollutants to the environment. Based on these circumstances, it is necessary to handle organic waste to use it as raw material biodigester. The aim of this study is to reduce the waste amount by managing waste in STT-PLN Campus with Anaerobic Digester Technology implementation. Stages in this study are sorting, burning and mixing. The method is turning waste into energy as we call Waste to Energy (WtO). This method has been developed in many developed countries. One of alternative to produce heat energy or electricity by using garbage or waste fuel, either livestock waste, agricultural waste, waste water, industrial waste, waste of human excrement and waste organic waste.Anaerobic Digester System is a system which offers potential energy savings is a more stable process for organic waste medium and high strength. Waste Anaerobic Digester plant-based biomass is very efficient in the utilization of renewable energy potential untapped gas from organic wastes into high calories. The methane gas produced from the biogas plant can be used with relative ease for power generation and industrial / domestic heating.